2006
DOI: 10.1002/dvdy.21010
|View full text |Cite
|
Sign up to set email alerts
|

Tbx1 regulation of myogenic differentiation in the limb and cranial mesoderm

Abstract: The T-box transcription factor Tbx1 has been implicated in DiGeorge syndrome, the most frequent syndrome due to a chromosomal deletion. Gene inactivation of Tbx1 in mice results in craniofacial and branchial arch defects, including myogenic defects in the first and second branchial arches. A T-box binding site has been identified in the Xenopus Myf5 promoter, and in other species, T-box genes have been implicated in myogenic fate. Here we analyze Tbx1 expression in the developing chick embryo relating its expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 79 publications
(112 reference statements)
3
63
1
Order By: Relevance
“…Tbx1 is expressed in both first and second BA at E9.5 and when mutated leads to severe perturbation or absence of both first and second BA muscles (11). Tbx1 also maintains the number of myocytes in the head and limb (35). Interestingly, like Pitx2, expression of Tbx1 follows the onset of myogenic commitment in the limb muscle anlagen but precedes the speciation event in the first BA muscle precursors (15).…”
Section: Discussionmentioning
confidence: 99%
“…Tbx1 is expressed in both first and second BA at E9.5 and when mutated leads to severe perturbation or absence of both first and second BA muscles (11). Tbx1 also maintains the number of myocytes in the head and limb (35). Interestingly, like Pitx2, expression of Tbx1 follows the onset of myogenic commitment in the limb muscle anlagen but precedes the speciation event in the first BA muscle precursors (15).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these genes could act both cell autonomously, as well as non-cell autonomously, to affect muscle development. That these genes also act cell autonomously to control myogenesis in head mesoderm has been supported by conditional knockout studies in mice (Aggarwal et al, 2010;Dastjerdi et al, 2007;Dong et al, 2006;Grifone and Kelly, 2007;Zacharias et al, 2011). However, additional conditional gene ablation studies are needed to assess cell-cell interactions in regulation of muscle cell fates.…”
Section: Pitx2 and Tbx1mentioning
confidence: 99%
“…This could be due to compensation by another factor. Likely candidates include: Pax7, which is expressed in precursors from E11.5 (Kassar-Duchossoy et al, 2005;Relaix et al, 2005); Tbx1, which is initially expressed in dorsal masses of the limbs (Dastjerdi et al, 2007) and reminiscent of residual MyoD expression observed in Pitx2;Myf5(Mrf4) mutants; and, finally, Pitx3, which is expressed after Pitx2 during embryonic myogenesis . Pitx3 does not compensate for loss of Pitx2 towards myogenin or MyoD expression in limbs (see Fig.…”
Section: Research Articlementioning
confidence: 99%
“…Although this core network has been implicated in all skeletal myogenesis, various studies on hierarchical interactions between MRFs and with upstream transcription factors such as Pax3 suggested that 'wiring' of the myogenesis network is different in trunk, limbs or head muscles (Bajard et al, 2006;Kablar et al, 1999;Kassar-Duchossoy et al, 2004;Sambasivan et al, 2009). In particular, different transcription factors were shown to modulate the core network in these muscles (Dastjerdi et al, 2007;Grifone et al, 2005;Grifone et al, 2007;Mankoo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%